Difficulties related to the design of research tools from the point of view of postgraduate students (Field study at the faculty of education at Tishreen University) - شحيده, اريج; بشرى شريبه; رامي أمون (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The current research aims to identify the difficulties faced by postgraduate students in designing their research tools. To achieve this goal, a questionnaire was developed, and the researcher followed the analytical descriptive approach. It was conducted on a sample of postgraduate students (Master's , Ph.D) at the faculty of education at Tishreen University, which consisted of 75 male and female students, and they were selected using a simple random method. The results showed that the difficulty of not providing the opportunity to access the sites of international libraries through the university was one of the most difficult difficulties faced by postgraduate students, and it came with a high degree, it was also noted that there were no statistically significant differences between the mean scores of master's and doctoral students on identifying difficulties in designing research tools.